An active, selective, and stable manganese oxide-supported atomic Pd catalyst for aerobic oxidation of 5-hydroxymethylfurfural. Issue 15 (18th July 2019) - Liao, Xuemei; Hou, Jindou; Wang, Ya; Zhang, Hao; Sun, Yu; Li, Xiaopeng; Tang, Siyang; Kato, Kenichi; Yamauchi, Miho; Jiang, Zheng
Abstract : An MnO2 -supported atomic Pd catalyst can actively, selectively and stably convert HMF into FDCA. Abstract : Here we report for the first time a Pd-MnO2 catalyst with a single-atom feature that can convert 5-hydroxylmethyfurfural (HMF) into the important bioplastic building block 2, 5-furandicarboxylic acid (FDCA) with a high yield of 88% in aqueous solution using O2 as an oxidant at ambient pressure. Pd-MnO2 shows higher activity in the productivity of FDCA (100.91 mmol h −1 gPd −1 ) than its Pd nanoparticle counterpart (45.57 mmol h −1 gPd −1 ) and state-of-the-art Pd-based catalysts. Pd-MnO2 displays promising recyclability with no degradation after five catalytic runs. Experimental and theoretical results suggest that the single-atom Pd sites that have enhanced binding affinity to HMF and their surrounding sites on the MnO2 support work synergistically toward HMF oxidation.